Confirmatory factor analysis and gender invariance of the Persian version of psychological control scale: association with internalizing and externalizing behavior problems - Habibi Asgarabad, Mojtaba; Salehi Yegaei, Pardis; Mokhtari, Sima; Izalnoo, Balal; Trejos-Castillo, Elizabeth (Frontiers in Psychology, 2023)
Introduction: Introduction: The current cross-sectional study aimed to examine the reliability, construct validity, gender invariance and concurrent validity of the psychological control scale-youth self-report (PCS-YSR) among Iranian adolescents. Methods: A total of 1453 high school students (49.2% boys; M age = 15.48, SD = 0.97), who aged between 14 and 18 years old completed the PCS-YSR and the youth self-report (YSR) scale of behavior problems. Results: Reliability was established using Cronbach’s alpha and ordinal alpha for maternal and paternal psychological control. The confirmatory factor analysis (CFA) results supported the original unidimensional model of the PCS-YSR scale for both mother and father forms. Results also revealed that mother and father forms of PCS-YSR were invariant across adolescents’ gender. When comparing the mean differences, mothers were more psychologically controlling toward their sons, compared to their daughters. The mother and father forms of PCS-YSR were found to have acceptable concurrent validity through their relationship to internalizing and externalizing behavioral problems. Discussion: Overall, our findings supported the psychometric properties of the Persian version of the Psychological Control Scale-Youth Self-Report among Iranian adolescents. This scale can be used as an efficient tool for parental psychological control among adolescents in Iran. The negative effect of the intrusive parenting behavior on child’ negative outcomes in Iran, irrespective of culture, was shown.